The cancer genome atlas pan-cancer analysis project - Weinstein, J.; Collisson, E.; Mills, G.; Shaw, K.; Ozenberger, B.; Ellrott, K.; Sander, C.; Stuart, J.; Chang, K.; Creighton, C.; Davis, C.; Donehower, L.; et al. (2013)
The Cancer Genome Atlas (TCGA) Research Network has profiled and analyzed large numbers of human tumors to discover molecular aberrations at the DNA, RNA, protein and epigenetic levels. The resulting rich data provide a major opportunity to develop an integrated picture of commonalities, differences and emergent themes across tumor lineages. The Pan-Cancer initiative compares the first 12 tumor types profiled by TCGA. Analysis of the molecular aberrations and their functional roles across tumor types will teach us how to extend therapies effective in one cancer type to others with a similar genomic profile. © 2013 Nature America, Inc. All rights reserved.